Detection of distributed denial of service attacks in cloud computing by identifying spoofed IP. (1st January 2013) - Jeyanthi, N.; Barde, Uttara; Sravani, M.; Tiwari, Venu; Iyengar, N.Ch. Sriman Narayana
Cloud computing is a booming field which will be predominating the IT industries soon. Cloud computing is a virtual dynamic version of the present day internet resource access which is static. Cloud computing provides high availability of various large-scale geographically distributed resources for users ranging from small to large-scale on demand. The two key advantages of this model are ease of use and cost effectiveness, i.e., cost as per the usage and maximum resource utilisation. The main issue identified in cloud computing is security. In the specific case of cloud computing systems, the impact of a flooding attack is expected to be amplified drastically as and when the cloud computing operating system notices the high workload on the flooded service, it will start to provide more computational power to cope with the additional workload. The attacker can flood a single, cloud-based address in order to perform a full loss of availability on the intended service. In this paper, the proposed spoofing detection algorithm to detect DDos attacks launched against a server inside a cloud.